Charles W. Thomas (1903-1973) - Reed, John C. (ARCTIC, 1974)
Rear Admiral Charles W. Thomas, U.S. Coast Guard (Retired) was born in Pasadena, California in 1903. On 3 March 1973 he and his wife were struck down and killed by a speeding car in Ushuaia, southern Argentina, while they were attempting to walk across the street. Admiral Thomas was well known in polar circles - both north and south. At the time of his death he was serving as lecturer and ice pilot on the passenger motor vessel Linblad Explorer, which was on a cruise to the Antarctic. . He will long be remembered as one of the polar "greats". He was elected a Fellow of the Arctic Institute in January 1959 for distinguished scientific service in the Arctic. He earned Masters' degrees in Marine Geology (Washington University) and Marine Biology (The University of Maryland). He was a qualified oceanographer. He is the author of papers on such diverse subjects as sea pollution, undersea research, polar navigation, and ship handling. His well-known book, Ice is Where You Find It, was published in 1951. Admiral Thomas, following his graduation from the Coast Guard Academy in 1924, rose steadily in rank and in responsibility in the Coast Guard, until his retirement as Rear Admiral in late 1957. In June 1943, Thomas was placed in command of the cutter Northland, which captured and destroyed a Nazi weather-radio station, and established a Naval Station on Jan Mayen Island. The following year found him in command of the heavy-duty, combat icebreaker Eastwind, and of a northeast Greenland Task Unit. Eastwind pursued through the icepack and captured the German armed trawler Externstiene, and another weather station on North Little Koldeway Island off the northeast coast of Greenland. For those exploits, the then Captain Thomas was awarded the Legion of Merit. Capt. Thomas became the Commander, Greenland Patrol, early in 1945. After the war, in 1946-1947, RADM Thomas commanded the icebreaker Northwind on the fourth Byrd expedition to the Antarctic, designated Operation High Jump. His ship cleared the way through the ice of ...